Crisi e Rigenerazione nella valle dell'Alto Khabur (Siria) La produzione ceramica nel passaggio dal Bronzo Antico al Bronzo Medio - ORSI, VALENTINA (Premio Tesi di Dottorato, 2011)
In the history and archaeology of the Ancient Near East, the period between the end of the third and the beginning of the second millennium BC in northern Mesopotamia constitutes a 'Media Aetas', an obscure period between the flourishing of the urban cultures of the Ancient Bronze Age in the middle of the III millennium BC and the development of the Amorite states of the Middle Bronze Age at the end of the 19th century BC. The identification in the archaeological sequence of Tell Barri, the ancient city of Kahat, of the ceramic horizon coeval with the 'urban crisis' that preceded the diffusion of the painted ceramic of Khabur, associated with a new phenomenon of sedentarisation, makes it possible to redefine the chronology of events in the region. It aso enables a delineation of the processes of interaction between the various social realities of northern Mesopotamia in the phase of formation that underlies the subsequent cultural development of the II millennium BC.